Empowerment of Women Farmers in the Utilization of Yard Land Through the RPL Concept in Cimaung District, Bandung Regency, Indonesia (PMIPA FKIP UNJA, 2025)
A yard is a plot of land around a house that can be utilized as a source of food potential to meet the food and nutrition needs of the family. The activity of utilizing yard land is carried out through the concept of Sustainable Food House (RPL), which is a household principle that utilizes yard land in an environmentally friendly way. The purpose of this research is to describe the level of empowerment, analyze the factors related to empowerment, and formulate appropriate strategies to enhance the empowerment of Women's Farmers' Groups (KWT) in utilizing yard land through the RPL concept in Cimaung District. This study was conducted from April 1, 2021, to June 30, 2021, in Cimaung District, Bandung Regency, West Java Province. The respondents in this study were members of women's farmers' groups from three villages, totaling 56 people, determined by purposive sampling method. Data were collected through observation, questionnaire distribution, interviews, and literature studies. The analysis used in this study was descriptive analysis and Spearman Rank correlation analysis. The analysis results show that the level of empowerment of the Women's Farmers' Group (KWT) is in the high category (64.3%). Factors related to the empowerment of KWT include yard area, the role of extension workers, the role of the government, infrastructure availability, and access to information. Strategies that can be used to improve the empowerment of KWT in utilizing yard land include enhancing the learning experience of female farmers and maximizing extension activities as well as demonstrations related to making plant-based pesticides and establishing RPL demonstration plots